Comparative risk assessment and cessation information seeking among smokeless tobacco users. (May 2018) - Jun, Jungmi; Nan, Xiaoli
Abstract: Introduction: This research examined (1) smokeless tobacco users' comparative optimism in assessing the health and addiction risks of their own product in comparison with cigarettes, and (2) the effects of comparative optimism on cessation information-seeking. Methods: A nationally-representative sample from the 2015 Health Information National Trends Survey (HINTS)-FDA was employed. Results: The analyses revealed the presence of comparative optimism in assessing both health and addiction risks among smokeless tobacco users. Comparative optimism was negatively correlated with most cessation information-seeking variables. Health bias (the health risk rating gap between the subject's own tobacco product and cigarettes) was associated with decreased intent to use cessation support. However, the health bias and addiction bias (the addiction risk rating gap between the subject's own tobacco product and cigarettes) were not consistent predictors of all cessation information-seeking variables, when covariates of socio-demographics and tobacco use status were included. In addition, positive correlations between health bias and past/recent cessation-information searches were observed. Conclusions: Optimisic biases may negatively influence cessation behaviors not only directly but also indirectly by influencing an important moderator, cessation information-seeking. Future interventions should prioritize dispelling the comparative optimism in perceiving risks of smokeless tobacco use, as well as provide more reliable cessation information specific to smokeless tobacco users. Highlights: Smokeless tobacco users showed comparative optimism about their health risks Tobacco users and non-users rated addiction risks of smokeless tobacco lower than cigarettes. The optimism was negatively correlated with cessation information seeking The optimism predicted decreased intent to use cessation support Optimism may influence cessation directly and indirectly moderated by information-seeking